2010
DOI: 10.1093/humrep/deq057
|View full text |Cite
|
Sign up to set email alerts
|

Cross border reproductive care in six European countries

Abstract: The cross border phenomenon is now well entrenched. The data show that many patients travel to evade restrictive legislation in their own country, and that support from their home health providers is variable. There may be a need for professional societies to establish standards for cross border reproductive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
202
0
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(217 citation statements)
references
References 13 publications
3
202
0
12
Order By: Relevance
“…Similar results were reported by Shenfield et al [12], who noted that the internet was the main source of information for Swedish, German, and British patients. Other sources included friends, relatives, and patient organizations; however, these were less important [12,22]. At the same time, a large number of study participants felt that they lacked information (41.0 %).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were reported by Shenfield et al [12], who noted that the internet was the main source of information for Swedish, German, and British patients. Other sources included friends, relatives, and patient organizations; however, these were less important [12,22]. At the same time, a large number of study participants felt that they lacked information (41.0 %).…”
Section: Discussionsupporting
confidence: 89%
“…Medical insurance does not cover infertility treatment domestically, and treatment abroad may result in enormous costs. Other studies have also reported that the cost of treatment abroad was a negative factor for CBRC [12,21]. Another negative factor indicated by some participants was the language barrier affecting the collecting of information and hindering communication with medical staff (51.0 %).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As we touched upon in our discussion on surrogate motherhood, the variation in regulations in Europe has given rise to the phenomenon of cross-border reproductive care (Shenfield et al 2010;Nygren et al 2010). Cross-border reproductive care refers to couples or individuals seeking assisted reproduction treatments in a country other than their country of permanent residence.…”
Section: Cross-border Reproductive Care In Europementioning
confidence: 99%